2014
DOI: 10.3389/fneur.2014.00030
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic Posterior Circulation Stroke: A Review of Anatomy, Clinical Presentations, Diagnosis, and Current Management

Abstract: Posterior circulation strokes represent approximately 20% of all ischemic strokes (1, 2). In contrast to the anterior circulation, several differences in presenting symptoms, clinical evaluation, diagnostic testing, and management strategy exist presenting a challenge to the treating physician. This review will discuss the anatomical, etiological, and clinical classification of PC strokes, identify diagnostic pitfalls, and overview current therapeutic regimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
186
0
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 208 publications
(215 citation statements)
references
References 107 publications
4
186
0
10
Order By: Relevance
“…Common mimics include VA dissection; vasculitis; reversible cerebral vasoconstriction syndrome; mitochondrial encephalopathy, lactic acidosis, and stroke-like episodes; and subclavian steal phenomenon or cardiac or paradoxical embolism. 22 BHS is a rare disorder and its management has not been standardized, but it is most often surgical. 5 An initial conservative approach may include neck immobilization using a cervical collar or neck brace.…”
Section: Discussionmentioning
confidence: 99%
“…Common mimics include VA dissection; vasculitis; reversible cerebral vasoconstriction syndrome; mitochondrial encephalopathy, lactic acidosis, and stroke-like episodes; and subclavian steal phenomenon or cardiac or paradoxical embolism. 22 BHS is a rare disorder and its management has not been standardized, but it is most often surgical. 5 An initial conservative approach may include neck immobilization using a cervical collar or neck brace.…”
Section: Discussionmentioning
confidence: 99%
“…22 Vertebral arterial dissection may present with occipital headaches and symptoms suggestive of brainstem or posterior circulation infarction. 23 Vascular imaging is paramount in diagnosis, and although digital subtraction angiography is considered the gold standard, vascular imaging with CTA or MRA are both acceptable techniques in the emergency department setting. 24 Antiplatelet therapy has been shown to be as effective as anticoagulation in treatment, and endovascular stabilization may be warranted in some cases.…”
Section: Reversible Cerebral Vasoconstrictive Syndrome (Rcvs) Is a CLmentioning
confidence: 99%
“…Prior research showed that only 3.2% of patients presenting with dizziness, vertigo or imbalance were diagnosed with a stroke or Transient Ischaemic Attack (TIA) [2]. Vestibular symptoms such as vertigo can be attributed to both peripheral causes such as vestibular neuritis or central causes like brainstem/cerebellar stroke.…”
mentioning
confidence: 99%